An insight into the anti-inflammatory properties of edible and medicinal mushrooms. (August 2018) - Du, Bin; Zhu, Fengmei; Xu, Baojun
Graphical abstract: Highlights: The anti-inflammatory properties of mushrooms were summarized. The cell model and animal model of anti-inflammatory activity were reviewed. Mechanisms of anti-inflammatory activity of mushrooms were summarized. Clinical studies on anti-inflammatory activity of mushroom were presented. Abstract: Background: Mushrooms have been valuable as edible and medical provisions for humankind. It is attributed not only to the quality of their taste but also to their biological activities. The extracts, compounds, and metabolites have a lot of biological activities such as antidiabetic, antioxidative, antitumor, and anti-inflammatory effects. The potent anti-inflammatory activity is associated with a multitude of signaling pathways. However, there are a few review papers on the anti-inflammatory activity of mushrooms. Scope and approach: Herein, the anti-inflammatory potential of mushroom is critically discussed using in vitro and animal models. Moreover, the mechanisms of anti-inflammatory activity are summarized. The current status of clinical studies evaluating anti-inflammatory activity of mushroom is also presented. Key findings and conclusion: It is believed that insights about these advances may encourage researchers to discover new phytochemical components and further study specific bioactivities of mushroom.